Calm the Core: A Study Protocol Exploring Biofeedback for Endometriosis Relief - Hajek Gross, Carola; Strobl, Elena; Weise, Cornelia (4. Deutscher Psychotherapie-Kongress 2025, 2025)
Theoretical Background: Endometriosis affects approximately 10% of individuals with a uterus in the reproductive age, leading to chronic pain and significant impairments in quality of life. Conventional medical treatments often provide limited long-term relief, and many individuals seek non-invasive, hormone-free alternatives. While promising psychotherapeutic approaches exist, they might not well enough address the patients’ predominantly somatic understanding of the condition. Preliminary non-controlled studies suggest that individuals with endometriosis may exhibit increased pelvic floor tension, which could contribute to the chronification of pain. Surface electromyography (sEMG)-biofeedback is a well-established method for real-time regulation of muscular activity and has shown promise in reducing muscle tension and improving self-efficacy in other chronic pain conditions. However, its application to endometriosis has not yet been explored. Aim: This study aims to evaluate the rationale and feasibility for using sEMG biofeedback as a treatment for endometriosis-related dysfunction. Methods: The study includes 30 individuals with endometriosis and 30 matched healthy controls. In the first step, a psychophysiological assessment will be conducted to measure baseline muscle tension, relaxation, and stress reactivity under different experimental conditions. Vaginal sEMG electrodes will be used to assess pelvic floor tension, while additional sensors will measure abdominal muscle tension and skin conductance levels. A MANOVA will be employed to examine group differences in muscle tension, with the primary aim of determining whether pelvic floor tension is elevated in the endometriosis group compared to the control group. In a second step, individuals with endometriosis will be randomly assigned to either a one-session, 20-minute sEMG biofeedback intervention or a 20-minute progressive muscle relaxation (PMR). Acceptance and feasibility of the sEMG biofeedback intervention will be evaluated via a post-intervention survey, focusing on participants’ perceived ability to modulate pelvic floor muscle tension, usability, and willingness to engage in future biofeedback training. Discussion: This pilot study will provide critical insights into the feasibility of sEMG-biofeedback for individuals with endometriosis, focusing on its applicability and acceptance. The findings will inform the design of a larger-scale randomized controlled trial aimed at evaluating the long-term benefit of sEMG-biofeedback in endometriosis, such as improvements in quality of life, self-efficacy, and pain interference. The results of the study could pave the way for implementing biofeedback as a means to better address the somatic component of endometriosis. Stichwörter: Endometriosis, sEMG-Biofeedback, Pelvic Floor Tension, Biopsychosocial Treatmen